Hierarchical imaging: a new concept for targeted imaging of large volumes from cells to tissues - Wacker, Irene; Spomer, Waldemar; Hofmann, Andreas; Hillmer, Stefan; Gengenbach, Ulrich; Schröder, Rasmus R. (BMC cell biology, 2016)
Imaging large volumes such as entire cells or small model organisms at nanoscale resolution seemed an unrealistic, rather tedious task so far. Now, technical advances have lead to several electron microscopy (EM) large volume imaging techniques. One is array tomography, where ribbons of ultrathin serial sections are deposited on solid substrates like silicon wafers or glass coverslips.